When Teams Become a Burden: A Study of Social Laziness and Work Productivity in Production Employees - Rizqisyah, Ariq; Rinaldi, Martaria Rizky (Journal of Social and Industrial Psychology, 2025)
Work productivity is a key indicator in achieving organizational goals, particularly in group-based work that requires active individual contributions. One challenge that can hinder productivity is social loafing, a tendency for individuals to exert less effort when working in groups than when working alone. This study aimed to examine the relationship between social loafing behavior and employee productivity. A quantitative approach with a non-experimental correlational design was employed. The study involved 94 production employees selected through purposive sampling, based on criteria: active employment status, a minimum of six months of work experience, and current involvement in team-based tasks. Data were collected using two psychological scales developed based on the theories of Chidambaram & Tung (social loafing) and Simamora (work productivity). Data analysis was conducted using Pearson correlation to examine the relationship between variables. The results indicated that the hypothesis was accepted, revealing a significant negative correlation between social loafing and work productivity (r = -0.628; p = 0.000). The coefficient of determination showed that social loafing accounted for 39.4% of the variance in employee productivity. The study concludes that higher levels of social loafing are associated with lower levels of work productivity. These findings underscore the importance of implementing individual-level evaluations within group work to reduce the emergence of social loafing and enhance accountability. This study contributes to the literature by expanding the examination of social loafing into real-world organizational settings, specifically among production employees in Indonesia, and provides practical insights for designing team structures that promote individual accountability.